The Impact of Political Risk on Sovereign Bond Spreads - Evidence from Latin America - Christoph Moser (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
Sovereign risk is defined as a country?s ability-to-pay and willingness-to-pay its debt. This paper examines how cabinet reshuffles affecting the ministry of finance or economics are perceived by sovereign bond holders in twelve Latin American countries from 1992 to 2005. We find that such political news instantaneously increases bond spreads. Furthermore, spreads trend significantly upward in the 40 days leading up to the minister change, before flattening out on a higher level in the 40 days thereafter. Evidence suggests that uncertainty about the future course of economic policy and the government?s willingness-to-pay increases refinancing costs for respective emerging markets.
Keywords: G14; H63; F34; F30; 330; political instability; country risk; bond spreads; Latin America; Portfolio-Investition; Öffentliche Anleihe; Politische Stabilität; Risiko; Öffentliche Schulden; Schätzung; Lateinamerika